STUDI KETERSEDIAAN DAN KEMAMPUAN MEMBAYAR ANGKUTAN UMUM KOTA KE KABUPATEN PEMEKARAN DI PROPINSI PAPUA-PAPUA BARAT - Thely S.H Sembor; Dewi Anggraeni (DINAMIS, 2014)
Transportation of publik transport of in city Shove is transportation which islocated in mother of Town of Provinsi Papua West. But transportation of publiktransport in Town Shove the the target regency in Maybrat and Arfak not yet ownedthe tariff which field is by what wanted by service ( society ), so also on the contrarycommon/ public transport cost from Regency of Maybrat, Arfak, Nabire and Supiori ofTown target Shove. So that/ to be transport cost of public treated by Government andOperator can there are balance require to be done/conducted or know the ability payfor the society of Ability To Pay ( ATP ) and willingness pay for the society ofWillingness To Pay (WTP) user of service of publik transport transportation.Doing/Conducting measurement of Ability To Pay (ATP), using method of householdbudget and Willingness To Pay ( WTP ) using method of State Preference. Result ofresearch that is estimate the average value of ATP and average value of WTP by 80%responden ready to overpay to the make-up of safety.